Analisis Kemampuan Mahasiswa dalam Merancang Modul Ajar Berdiferensiasi dalam Pembelajaran Micro Teaching di PGMI - Agustia, Putri; Jannah, Misbahul; Oviana, Wati (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2026)
Students are required to master the subject matter and also create teaching modules that follow differentiated learning guidelines. This aligns with the objectives of the Merdeka Curriculum, which prioritizes student-centered learning. The purpose of this study was to analyze students' abilities in developing differentiated teaching modules. The method used in this research is a quantitative descriptive method. The subjects were 16 student teachers in the even semester of the 2024/2025 academic year. The research instrument was a differentiated teaching module assessment instrument sheet. The teaching module documents were collected and then analyzed using descriptive statistics with percentage techniques, which were interpreted into scores. Based on the analysis results, students' abilities in designing differentiated teaching modules at PGMI are classified as good and lacking, with a score of 37% for differentiated learning mapping, 73% for general information, 72% for core competencies, and 33% for attachments. This demonstrates the need for the PGMI study program to develop specific training related to differentiated learning mapping and the development of teaching modules, as well as to strengthen lecturer support for students' teaching module design assignments. The results of this study can serve as a basis for curriculum evaluation and the development of learning tools to enhance the competency of PGMI students. Keywords: Differentiated Learning, Teaching Module, Independent Curriculum